Pendekatan Ibn Ḥajar al-ʿAsqalānī dalam Menyantuni Ḥadīth-Ḥadīth yang Menyanggah Ṣaḥīḥ al-Bukhārī:Sorotan Fatḥ al-Bārī bi SharḥSaḥīḥ al-Bukhārī - Ahmad Izzuddin Abu Bakar (Institute of Islamic Understanding Malaysia (IKIM), 2024)
TAFHIM: IKIM Journal of Islam and the Contemporary World Volume 16 No.2 Page (151-174)